The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fpsyg.2019.01774
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structures of General Health Questionnaire-12 Within the Number of Kins Among the Rural Residents in China

Abstract: The 12-item general health questionnaire (GHQ-12) has been extensively used with Chinese population. Yet, it has not been used from a national representative survey in rural China. The aim of this study was to examine how number of kins associated with the factor structures of the CHQ-12 among the rural residents in China. Data were obtained from the 2009 rural-to-urban migrants survey (RUMiC). Exploratory factor analysis (EFA) (principal component analysis with varimax rotation) was performed to identify fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 72 publications
1
12
0
Order By: Relevance
“…Item responses range from 0 to 3, and the overall score ranges from 0 to 36, with more than 12 being defined as cases (12). The Chinese version has been validated in different groups of Chinese (13)(14)(15).…”
Section: Measurementsmentioning
confidence: 99%
“…Item responses range from 0 to 3, and the overall score ranges from 0 to 36, with more than 12 being defined as cases (12). The Chinese version has been validated in different groups of Chinese (13)(14)(15).…”
Section: Measurementsmentioning
confidence: 99%
“…Each GHQ-12 item has 4-point responses: 'not at all = 0', 'same as usual = 1', 'rather more than usual = 2', and 'much more than usual = 3', such as "feeling nervous and strung up all the time" and "enjoying daily activities".The GHQ-12 score, obtained by summing up the scores of the 12 items, measures the severity of minor psychiatric morbidity [43,44]. The Chinese GHQ-12 is reliable and valid in the Chinese population [44,45]. In the present study, Cronbach's α was 0.86.…”
Section: Measurement Of Psychological Distressmentioning
confidence: 55%
“…Additionally, several studies have demonstrated that its Chinese version has satisfactory reliability, good sensitivity, and high specificity for assessing mental disorders. 23 , 24 Therefore, the GHQ-12 has been adopted widely. 25 , 26 The scores for responses to positive statements were 0=better than usual or same as usual, and 1=less than usual or much less than usual.…”
Section: Methodsmentioning
confidence: 99%